Malaysian homestay programme in Selangor: A case study of Banghuris homestay / Muhammad Hanif Othman - Othman, Muhammad Hanif (2022)
Tourism industry development has always been considered as an important agenda for Malaysian development as tourism promotes the sustainability and well-being of local communities. Thus, the involvement of local communities in the tourism industry is a government strategy to help poor communities in rural areas. Local communities can improve their economic status by participating in the tourism sector through the homestay programme. The homestay programme is becoming Malaysia’s main tourism product. In 1997, 286 operators participated in the programme. That number increased to 2,533 operators in 2007, and became 4,313 operators in Jun 2022, revealing the rural community’s increased interest and participation in this new community-based tourism.